التقعيد الفقهي عند ابن تيمية من خلال كتابه "القواعد النورانية" : دراسة منهجية تحليلية - Muhamad Mustakim Abd. Halim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research is about the forming of Fiqh maxims in the al-Qawa'id al-Nuraniyyah written by Shaykh al-Islam Ibn Taymiyyah identifying his method in forming the Fiqh maxims in his book, revealing the characteristics of the method in addition to extracting the Fiqh maxims which are used to discover the concepts or ideas of Ibn Taymiyyah in forming Fiqh maxims. To collect data, the researcher used analytical and deductive methods to review past studies that give basic understanding of the topic. The researcher has found the following important results. Firstly, Ibn Taymiyyah's method in forming the Fiqh maxims is based on perfect, congruous and strong bases and principals which indicate the perfection and firmness of his method. Secondly, the disagreement between the Shaykh and other scholars in forming the Fiqh maxims is due to their disagreement in Usul al-Fiqh, specifically in the Shari'ah evidence and the Usul al-Fiqh principles. Thirdly, the Shaykh's method in deducting the evidence and extracting the meanings and reasons from the evidence indicate that he was a great scholar in many fields and he has comprehensive knowledge about the method of deducting and extracting from the evidence. Although he is considered a mujtahid who has his own opinions, but he is still known as a follower of Imam Ahmad due to the similarity between the two of them in their Shari'ah essentials. Lastly, everyone who attentively examines his method in forming the Fiqh maxims will find that the purpose of his method is to adhere to the Shari'ah method by choosing it over any other methods and by applying it in every aspect of life to achieve bliss in this lifetime and the hereafter.